(untitled) (Theatrum historiae, 2025)
This overview study explores the National Movement of Working Youth (Národní hnutí pracující mládeže, NHPM) as a historically under-researched case of left-wing youth resistance during the period of the Protectorate of Bohemia and Moravia. Framed within the historiographical development of scholarship on the Second World War and resistance in Czechoslovakia, the article highlights the neglect of youth as a distinct historical and political subject. The paper analyses the origins, ideological orientation, and organisational transformation of the NHPM from its legal existence during the Second Republic to its illegal activities following the occupation in March 1939. Emphasis is placed on the role of the illegal press, inter-organisational cooperation, and internal tensions within the movement. The study also reflects on the methodological challenges related to source fragmentation and advocates the fuller integration of youth movements into broader research on resistance, political culture, and everyday life under totalitarian regimes.